2021
DOI: 10.1016/j.heliyon.2021.e08124
|View full text |Cite|
|
Sign up to set email alerts
|

PRAK-03202: A triple antigen virus-like particle vaccine candidate against SARS CoV-2

Abstract: The rapid development of safe and effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) is a necessary response to coronavirus outbreak. Here, we developed PRAK-03202, the world’s first triple antigen virus-like particle vaccine candidate, by cloning and transforming SARS-CoV-2 gene segments into a highly characterized S. cerevisiae -based D-Crypt™ platform, which induced SARS CoV-2 specific neutralizing antibodies in BALB/c mice. Immunization using thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The S, E, and M proteins from the surface capsid of SARS-CoV-2 viruses are important vaccine targets. Saumyabrata et al [80] reported the recombinant co-expression of three proteins (S, E, and M) in an engineered brewer's yeast platform (D-Crypt™) that self-assembles into virus-like particles (VLPs). This design, as a multi-antigen VLP for SARS CoV-2, has the potential to be a scalable vaccine candidate.…”
Section: Current Status Of Research On Vlps Vaccines Against Covid-19mentioning
confidence: 99%
“…The S, E, and M proteins from the surface capsid of SARS-CoV-2 viruses are important vaccine targets. Saumyabrata et al [80] reported the recombinant co-expression of three proteins (S, E, and M) in an engineered brewer's yeast platform (D-Crypt™) that self-assembles into virus-like particles (VLPs). This design, as a multi-antigen VLP for SARS CoV-2, has the potential to be a scalable vaccine candidate.…”
Section: Current Status Of Research On Vlps Vaccines Against Covid-19mentioning
confidence: 99%
“…It is a Micro-Needle Array (MNA) based vaccine containing recombinant immunogens, namely, rSARS-CoV-2 S1 and rSARS-CoV-2-S1fRS09 [53].…”
Section: Pittcovaccmentioning
confidence: 99%
“…These units remarkably resemble wild type viruses without being infectious. The use of eukaryotic expression system has allowed researchers to develop various prophylactic VLP-based vaccine candidates for a few highly pathogenic viruses such as HIV (3), severe acute respiratory syndrome (SARS) (4)(5)(6) , Ebola virus (7,8), dengue fever virus (9)(10)(11), chikungunya virus (CHIKV) (12,13), Rift Valley fever virus (RVFV) (14) and HCV (15,16). Vaccines that use VLPs are safer than inactivated or attenuated viruses as the chances of virus reversion or incomplete inactivation is avoided.…”
Section: Introductionmentioning
confidence: 99%